Use and exchange of genetic resources of penaeid shrimps for food and aquaculture - John A. H. Benzie (Reviews in Aquaculture, 2009)
Penaeus (Litopenaeus) vannamei Boone, 1931 and Penaeus monodon Fabricius, 1798 provide 87% of the world’s farmed marine shrimp, and 99% with another five species, Penaeus (Fenneropenaeus) chinensis (Osbeck, 1765), Penaeus (Fenneropenaeus) indicus Milne‐Edwards, 1837, Penaeus (Fenneropenaeus) merguiensis de Man, 1888, Penaeus (Litopenaeus) stylirostris Stimpson, 1874 and Penaeus (Marsupenaeus) japonicus Bate, 1888. Genetically improved strains have been traded for P. chinensis , P. stylirostris , P. vannamei and P. monodon , although closed populations have been developed for all seven species. To date, domesticated strains have played a dominant role in seed production for only P. vannamei and P. stylirostris . Extensive worldwide transfer of wild and/or domesticated stocks has occurred for these two species and for P. monodon , but the volume and extent of transfer of the other species is less. Genetic variation documented in wild stocks does not appear to be threatened, but variation within cultured stocks is often reduced relative to the wild and has affected performance in some (now mostly defunct) cultured populations. Hybridization is not effective in producing useful shrimp strains. There is no organized banking of penaeid shrimp genetic resources, either as live shrimp, frozen tissue, tissue or cell culture or DNA. Open access DNA sequences are available, although limited for most species. Significant expressed sequence tags and large insert libraries are available only for P. vannamei and P. monodon .